The Effect of Spinal Muscle Fatigue and Psychosocial Factors on Pressure-Pain Threshold in Healthy Adults - Susan Mais; Jo Armour Smith (Pain Research and Management)
Objective. Pain sensitivity decreases following isometric exercise. It is not clear whether this exercise-induced hypoalgesia (EIH) occurs to the same extent in men and women. It is also unclear if the effect is systemic or local to the exercised musculature. The aim of our study was to investigate whether fatiguing isometric exercise of the spinal and hip extensors would result in increased pressure pain threshold (PPT) at sites local to and remote from the exercised muscles in healthy men and women and whether there is a relationship between central sensitization, psychosocial factors, and PPT. Subjects. 35 healthy adults (age 27.1 ± 4.5 years, 22 women). Methods. This was a within-subjects cohort study. Participants completed questionnaires quantifying central sensitization, pain catastrophizing, sleepiness/insomnia, anxiety, and depression. PPT was assessed at the lumbar and thoracic paraspinals, hamstrings, gastrocnemius, wrist, and third digit before and immediately after participants performed the Biering–Sorensen test to failure. Results. PPT increased postexercise in the thoracic paraspinals, hamstrings, and gastrocnemius in men and women and in the lumbar paraspinals in men only but did not change at the wrist and digit sites. A lower average PPT at baseline was associated with a higher central sensitization scores. A greater increase in average PPT postfatigue was significantly associated with higher average PPT at baseline. Conclusions. Exercise-induced hypoalgesia occurs at sites overlying the muscles involved in fatiguing exercise, but not at remote sites, and is more evident in males than females. The magnitude of EIH depends upon baseline PPT. Even in healthy individuals, greater central sensitization is associated with lower baseline PPT.